Human-Artificial Intelligence in Management Functions: A Synergistic Symbiosis Relationship - Xhavit Islami; Enis Mulolli (Applied Artificial Intelligence)
This review paper aims to investigate how the mutual interaction of artificial intelligence (AI) and human intelligence (HI) affects management functions. To achieve this, we use a question-based approach and a systematic literature review to elucidate the potential for AI and HI to interact and create a mutually beneficial symbiotic effect in management functions. We underscore the main issues that organizations must consider when transitioning to AI management. Specifically, in this review paper, we highlight the interaction between AI and HI; the investigation of this relationship in management functions such as planning and decision-making, organizing, leading, and controlling; the mutually beneficial impact of this symbiotic relationship in management; and possible ethical dilemmas. The paper concludes by identifying gaps in the existing literature, providing practical advice on integrating AI into various management functions, and exploring approaches that highlight specific areas requiring attention in future research.